Match and training injuries in Rugby League: A review of published studies - King, D. A.; Hume, P. A.; Milburn, P. D.; Guttenbeil, D. (Sports Medicine, 2010)
Rugby league is an international collision sport played by junior, amateur, semiprofessional and professional players. The game requires participants to be involved in physically demanding activities such as running, tackling, passing and sprinting, and musculoskeletal injuries are common. A review of injuries in junior and senior rugby league players published in Sports Medicine in 2004 reported that injuries to the head and neck and muscular injuries were common in senior rugby league players, while fractures and injuries to the knee were common in junior players. This current review updates the descriptive data on rugby league epidemiology and adds information for semiprofessional, amateur and junior levels of participation in both match and training environments using studies identified through searches of PubMed, CINHAL, Ovid, MEDLINE, SCOPUS and SportDiscus® databases.